Reconsidering the role of blood-brain barrier in Alzheimer’s disease: From delivery to target - Sousa, João André; Bernardes, Catarina; Bernardo-Castro, Sara; Lino, Miguel; Albino, Inês; Ferreira, Lino; Brás, José; Guerreiro, Rita; Tábuas-Pereira, Miguel; Baldeiras, Inês; Santana, Isabel; Sargento-Freitas, João (Frontiers in Aging Neuroscience, 2023)
The existence of a selective blood-brain barrier and neurovascular coupling are two unique central nervous system vasculature features that result in an intimate relationship between neurons, glia, and blood vessels. This leads to a significant pathophysiological overlap between neurodegenerative and cerebrovascular diseases. Alzheimer’s disease (AD) is the most prevalent neurodegenerative disease whose pathogenesis is still to be unveiled but has mostly been explored under the light of the amyloid-cascade hypothesis. Either as a trigger, bystander, or consequence of neurodegeneration, vascular dysfunction is an early component of the pathological conundrum of AD. The anatomical and functional substrate of this neurovascular degeneration is the blood-brain barrier (BBB), a dynamic and semi-permeable interface between blood and the central nervous system that has consistently been shown to be defective. Several molecular and genetic changes have been demonstrated to mediate vascular dysfunction and BBB disruption in AD. The isoform ε4 of Apolipoprotein E is at the same time the strongest genetic risk factor for AD and a known promoter of BBB dysfunction. Low-density lipoprotein receptor–related protein 1 (LRP-1), P-glycoprotein, and receptor for advanced glycation end products (RAGE) are examples of BBB transporters implicated in its pathogenesis due to their role in the trafficking of amyloid-β. This disease is currently devoid of strategies that change the natural course of this burdening illness. This unsuccess may partly be explained by our misunderstanding of the disease pathogenesis and our inability to develop drugs that are effectively delivered to the brain. BBB may represent a therapeutic opportunity as a target itself or as a therapeutic vehicle. In this review, we aim to explore the role of BBB in the pathogenesis of AD including the genetic background and detail how it can be targeted in future therapeutic research.